The Influence of Work Discipline and Work Motivation on Employee Work Productivity at Tompobulu District Office, Gowa District - Mutia, Nurul; Musa, Muhammad Ichwan; Wardhana Haeruddin, Muhammad Ilham; Tawe, Amiruddin; Dipoatmodjo, Tenri S.P. (PT. Maju Malaqbi Makkarana, 2023)
The aim of this research is to determine the influence of work discipline and employee work motivation at the Tompobulu sub-district office, Gowa Regency. The sample in this study was the entire population at the Tompobulu Subdistrict Office, Gowa Regency, 31 employees with a quantitative research type.f. The data used is primary and secondary data which was obtained using questionnaire distribution techniques.The results of the research after the data were processed with SPSS.13 show that there is a positive influence between the variables Work Discipline (X1) and Work Motivation (X2) on work productivity (Y) which can be shown through the multiple linear regression equation, namely Y= 4.087 + 0.733 X1 + 0.133 X2 + eand has a significant effect withThe calculated t value for each variable is 14.786 > t table (x1) and 2.134 > t table (X2), with the tarefsignifiction 0.000 < 0.05 (x1) and 0.042 < 0.05 (x2). Then the R square value is 0.885, this figure shows that the work discipline and work motivation variables contribute 88.5% and 21.5% are influenced byfactorothers not discussed in this study.